Obtaining of the absorption curve for the FB-17 tomato hybrid - Quesada-Roldán, Gustavo (REVISTA TERRA LATINOAMERICANA, 2013)
A nutrient accumulation or uptake curve of the FB-17 tomato hybrid was obtained during a crop cycle in a commercial plantation in San Isidro de Heredia, Costa Rica. The content of N, P, K, Ca, Mg and S was determined in 13 samples of three sections of the plant: root, aerial part and fruit. The nutrient accumulation curve for this hybrid was based on concentrations of these nutriments and dry weight of the plant sections. Nutriment ext raction was calculated considering a density of 19 230 plants ha-1 and an approximate yield of 162 Mg ha-1. The element extracted in the largest quantity was K with 762 kg ha-1, followed by N with 522, Ca (364), Mg (93), S (79) and P (39 kg ha-1). The greatest demand for all the elements was at 130 days, period significant in fruit set and fill; fruiting alone further explains the variations in demand by nutriments. Towards the end of the production cycle an accumulation of N, P and K was observed mainly in fruit, while most of Ca, Mg and S remained in the aerial part of the plant. The high nutriment requirements of the FB-17 hybrid respond to a yield expectation of 100 Mg ha-1, and constitute the minimum that must be supplied to the plant by fertilization to ensure optimum production.